Protein Synthesis in Simian Virus 40-Infected Monkey Cells - Walter, Gernot (1972)
The proteins of purified Simian virus 40 (SV40) were examined by sodium dodecyl sulfate-acrylamide gel electrophoresis and compared with the polypeptides synthesized in SV40-infected monkey cells. Purified virions contain two major components, with molecular weights of 44,000 and 31,000. Together they make up 83% of the total virion proteins. In addition, the virus contains 12 minor polypeptides, which are believed to be cellular proteins, or peptides derived from proteolytic degradation of the 44,000 molecular weight polypeptide. Pulse-label experiments show that about 90% of the polypeptides synthesized after SV40 infection are host-cell proteins; 10% represent the two major structural components of the virion. A small fraction (about 0.5%) consists of three polypeptides (molecular weights 70,000, 60,000, and 8,000) that are neither part of the virion nor detectable in uninfected cells. They are either virus-induced cellular proteins or, more likely, proteins coded for by the SV40 genome.